Highly Efficient Near‐Infrared Delayed Fluorescence Organic Light Emitting Diodes Using a Phenanthrene‐Based Charge‐Transfer Compound. (7th September 2015) - Wang, Shipan; Yan, Xianju; Cheng, Zong; Zhang, Hongyu; Liu, Yu; Wang, Yue
Abstract Significant efforts have been made to develop high‐efficiency organic light‐emitting diodes (OLEDs) employing thermally activated delayed fluorescence (TADF) emitters with blue, green, yellow, and orange–red colors. However, efficient TADF materials with colors ranging from red, to deep‐red, to near‐infrared (NIR) have been rarely reported owing to the difficulty in molecular design. Herein, we report the first NIR TADF molecule TPA‐DCPP (TPA=triphenylamine; DCPP=2, 3‐dicyanopyrazino phenanthrene) which has a small singlet–triplet splitting (ΔEST) of 0.13 eV. Its nondoped OLED device exhibits a maximum external quantum efficiency (EQE) of 2.1 % with a Commission International de L′Éclairage (CIE) coordinate of (0.70, 0.29). Moreover, an extremely high EQE of nearly 10 % with an emission band at λ=668 nm has been achieved in the doped device, which is comparable to the most‐efficient deep‐red/NIR phosphorescent OLEDs with similar electroluminescent spectra.